If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7k + -63 = 9k + -45 + -14k Reorder the terms: -63 + -7k = 9k + -45 + -14k Reorder the terms: -63 + -7k = -45 + 9k + -14k Combine like terms: 9k + -14k = -5k -63 + -7k = -45 + -5k Solving -63 + -7k = -45 + -5k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '5k' to each side of the equation. -63 + -7k + 5k = -45 + -5k + 5k Combine like terms: -7k + 5k = -2k -63 + -2k = -45 + -5k + 5k Combine like terms: -5k + 5k = 0 -63 + -2k = -45 + 0 -63 + -2k = -45 Add '63' to each side of the equation. -63 + 63 + -2k = -45 + 63 Combine like terms: -63 + 63 = 0 0 + -2k = -45 + 63 -2k = -45 + 63 Combine like terms: -45 + 63 = 18 -2k = 18 Divide each side by '-2'. k = -9 Simplifying k = -9
| 5(3x-4)-2=5(x-4)+28 | | 16x-16=x+8 | | b-2(b-2)=0 | | 5(-3-4)= | | -22x+11=-15x-45 | | 3x^4-4x^3+x^2+6x-2=0 | | 2(3x+1)-6=-2 | | 3(x+4)=2(x+10) | | 16+2=-56 | | 9x=27+8x | | 9-t-3(t+3)=0 | | 2n+n+5=20 | | 2(y+3)=-2(5y-1)+6y | | 3x-12=9x-36 | | 2(3x+1)-6=2 | | 39-5x-5(7-46x)=-12 | | 11x+3=-7x-8 | | 17x-8x+1=000 | | 6m-2m-4=-6 | | 3x^2=12x+12 | | 4(-m-6n)= | | 4+2(2x-1)=-2(8x-3)+6x | | X^2-1x-86=2 | | 4(23m-1)-8-32m=-2 | | -15x-12=-8x-19 | | 2(1-5x)=2(3x+2) | | X+y=4000-.08 | | X-9=9-x | | 16x-8x+1=000 | | 3x^2+3y^2-10x+3=0 | | 2(1-5x)=(3x+2) | | 4u-8+2(4u+4)=-4(u+3) |